1987
DOI: 10.1007/bf01044835
|View full text |Cite
|
Sign up to set email alerts
|

Juror decision making: The importance of evidence.

Abstract: Much of the research on juror decision making is concerned with whether jurors are swayed by irrelevant--or extralegal--issues in their judgments of defendants. Such studies examine whether jurors' attitudes and victims' and defendants' characteristics have a measurable impact on these decisions. Yet, in the typical study, evidential issues are either poorly measured or ignored, hence the effects of extralegal issues may be exaggerated. Moreover, jury simulations are often chosen to study these questions despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 39 publications
6
92
1
Order By: Relevance
“…In summary, subjects were more likely to find the defendant liable when there was strong evidence that the prescribed birth control pills could cause ovarian cancer. This result shows that subjects were properly sensitive to variations in the strength of the formally presented evidence (Kalven and Zeisel, 1996;Visher, 1987). Thus, in this case, the effect of causal evidence is rational and not an anchoring bias.…”
Section: Liability and Causationmentioning
confidence: 52%
“…In summary, subjects were more likely to find the defendant liable when there was strong evidence that the prescribed birth control pills could cause ovarian cancer. This result shows that subjects were properly sensitive to variations in the strength of the formally presented evidence (Kalven and Zeisel, 1996;Visher, 1987). Thus, in this case, the effect of causal evidence is rational and not an anchoring bias.…”
Section: Liability and Causationmentioning
confidence: 52%
“…Visher (1987), citing works by Hans and Vidmar (1982), Hastie, Penrod et al (1983), and Hepburn (1980) point out that while juror demographic characteristics--age, gender, race, occupation--are statistically related to jurors' judgments of the defendant, they are not strong enough to predict verdicts (p.3). Visher's 1987 study of 331 jurors in 38 sexual assault trials revealed that jurors' demographics--age, race and sex--seem unrelated to judgments of defendant guilt; psychographic variables, however, such as juror beliefs in the need for harsher sentences and stricter laws increased the likelihood of guilty verdicts.…”
Section: Evidence From Literaturementioning
confidence: 99%
“…Concern for juror effectiveness led one federal judge, with consent of all parties, to experiment with selecting jurors on the basis of educational background (p.319). Several writers have addressed the jury competence issue, including Kalven and Zeisel (1966), Kalven (1964), Visher (1987), Kadish and Kadish (1971), Scheflin and Van Dyke (1980) , Williams (1963) and Greene (1983). Visher (1987) posits the most serious criticism of the jury system is that jurors are not competent to impartially consider evidence and decide issues of fact.…”
Section: Evidence From Literaturementioning
confidence: 99%
“…It is also worth emphasizing that the most important factor in juror decision making is the strength of the evidence (Eisenberg & Wells, 2002;Visher, 1987). Consequently, significant effects on dichotomous outcome variables (guilt/innocence, liability/no liability) should be expected only when the other evidence is closely balanced, which it was sometimes not (e.g., Kassin & Garfield, 1991).…”
Section: Limitations Of the Researchmentioning
confidence: 99%